Мультимоделювання як інструмент дослідження процесів у системі «полімерна мембрана – вода» - Заграй, Я.М.; Котовенко, О.А.; Мірошниченко, О.Ю. (Екологічна безпека та природокористування, 2012)
On the basis of multidesigns principle and quantification multimodels of processes, which pass on the border of phases in the system "podimeric membrane – water", in which a determining component is a multi-layered polymeric membrane the pores of which appear as a result of fluctuations of structural chainlets of polymers are synthesized. Job performances are directed on the decision of one of basic problems of ecology – preparations of drinking water as bases of ecosafety of vital functions and health of man.